Organizational Competence and Organizational Commitment Affecting Life Quality Development of Commissioned Officer in the 18th Army - Uangwara, Pongphob; Khanthahat, Phamorn; Yeunyong, Tanisorn (Rajapark Journal, 2022)
The objectives of this study were: 1) To study the level of organizational competency; 2) To study organizational competence and organizational commitment that affect the improvement of the working quality of life of non-commissioned officers. in the 18th Army Region 3) To propose guidelines for improving the quality of working life of commissioned officers in the 18th Army Region. This is quantitative and qualitative research. The sample group was commissioned, officers. In the 18th Army Region, 183 people used questionnaires and in-depth interviews as research tools. Statistical analysis such as frequency, percentage, mean, standard deviation Multiple Regression analysis, and correlation analysis The results of the study showed that 1) The level of organizational competency in the overall picture was at a high level, namely the shared values. strategic organizational structure form of management, personnel, operational system, and skills, respectively, and organizational commitment. The overall picture is at a high level, namely the investment of the individual. job search behavior relationships at work and the features of the work and the overall quality of working life development were at a high level. 2) Organizational competency and strategic commitment to the organization management style and shared values affect the development of quality of life at work statistically significant at the .05 level 3) Adjusting the management model based on shared values ​​to improve the quality of life and happiness at work for good health. both physically and mentally.